Encumbrances of rights to real estate as objects of registration in the legal cadaster - Ilyassova, K.М.; Kaziyeva, G.T. (Bulletin of the Karaganda University “Law Series”, 2022)
The article is devoted to the definition of the concept, the legal nature and types of encumbrances on rights to real estate, the criteria for their differentiation from other restrictions on rights to real estate and the boundaries of law, as well as issues of state registration of encumbrances of rights to the specified property. It is substantiated that the content of the right within its boundaries (limits) cannot be considered as its encumbrances. Also, encumbrances of rights to real estate should be distinguished from cases of forced termination of rights to it, since in the case of encumbrances of the right, the subject retains rights in respect of subject’s property, while in the other specified case, the termination of the right takes place. One of the criteria for distinguishing the types of encumbrances of rights to real estate is the presence or absence of rights of third parties to such property. Particular importance is attached to the differentiation of property encumbrances from obligations following the fate of real estate. It is substantiated that the list of encumbrances of rights to real estate subject to state registration cannot be exhaustive in the law, but the concept of encumbrance provided in the law should allow such a list to be determined.